Triphasic training. A systematic approach to elite speed and explosive strength performance - Dietz, C.; Peterson, B. (Bye Dietz Sport Enterprise, 2012)
Triphasic Training is the pinnacle of sports performance training. That`s not hype. Cal Dietz, strength coach at the University of Minnesota, has the results to back up this claim - a Hobey Baker Award winner, two Big Ten Athletes of the Year, over 400 All-Americans, 28 Big Ten/WCHA championship teams, 7 NCAA National Team Champions, and 13 teams that finished in the top four in the nation.